HETEROGENEITY IN CANCER RISK ASSOCIATED WITH ANTIHYPERTENSIVE DRUG USE: A META-ANALYSIS OF LOSARTAN AND AMLODIPINE - Adehi, Mary U; Nweze , Obini Nweze; Audi , Najib Isyaku; Bilkisu , Maijama’a (Economics and Statistics Research Journal (ESRJ), 2025)
Antihypertensive medications are among the most widely prescribed drugs globally. Although their efficacy in managing hypertension and preventing cardiovascular diseases is well established, concerns about their potential long-term adverse effects, including carcinogenicity, have emerged. This meta-analysis evaluated the relationship between antihypertensive drug use—particularly losartan and amlodipine—and the risk of developing cancer. A systematic review and meta-analysis were conducted following the PRISMA guidelines. Relevant studies published up to 2023 were identified through electronic databases. The analysis included studies reporting odds ratios (ORs) for cancer risk associated with any antihypertensive use, prolonged losartan use, or amlodipine use. Pooled effect estimates were calculated using both fixed-effect and random-effects models. Heterogeneity was assessed using Cochran’s Q, I², and τ² statistics, and Galbraith plots were used for visual inspection of variability. Sixty-two studies were included. The pooled random-effects OR for all antihypertensive medications was 1.14 (95% CI: 1.03–1.25), indicating a modest but statistically significant increase in cancer risk. The OR for losartan was 1.16 (95% CI: 0.88–1.53), which was not statistically significant due to extreme heterogeneity (I² = 94.1%). Amlodipine use was significantly associated with cancer (OR = 1.17, 95% CI: 1.05–1.30). Considerable heterogeneity was observed across all analyses (I² > 75%). This study showed a modest increase in cancer risk associated with the use of antihypertensive drugs, particularly amlodipine. However, the results for losartan were inconclusive due to the high variability among studies. Although the findings do not warrant immediate changes in clinical practice, they highlight the need for long-term pharmacovigilance and further investigation into drug-specific cancer risks.